Peningkatan Kemandirian Ekonomi Panti Sosial DKI Jakarta Melalui Integrasi Budidaya Maggot dan Budidaya Lele - Septiani, Winnie; Hartini; Suryana, Yunita Friscillia; Maulidya, Rahmi; Dewayana, Triwulandari Satitidjati (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Latar Belakang: Social care facilities are currently a cost center for the government, so the economic self-sufficiency of social care facilities needs support from various parties. This Community Service activity aims to provide assistance and business training through the integration of Maggot cultivation and catfish farming. This activity is a continuation of a previous program that has produced a mini Maggot cultivation plant and its training. Methods: The approach used is green entrepreneurship with a sustainable business model on three aspects: economic, social, and environmental. The stages of the activity include survey and evaluation of the results of previous activities, assistance in building catfish ponds, catfish pond fertilization, catfish fingerling stocking, catfish farming training, and activity evaluation. Results: The Maggot livestock produced from the previous program will be used as catfish feed. Maggots have high protein content that is beneficial for catfish growth. Two ponds, each with a 3 m diameter, are constructed and filled with 1000 catfish fingerlings. Conclusions: The caretakers of the facility and the residents of the facility are very enthusiastic and have responded very positively to this assistance and training program. The hope is that this program can encourage the facility to become entrepreneurs while considering green business aspects and providing positive social impacts.